METHODS OF ELECTRONIC EDUCATIONAL ENVIRONMENT AS A FACTOR OF IMPROVING THE QUALITY OF EDUCATION AT THE UNIVERSITY - Yunusova D.I. TSPU (PT. Antis International Publisher, 2024)
Abstract. In this article, clarified teaching methods appropriate for use in environment based on the analysis of scientific research on the electronic educational environment in the system of higher education.